CONCEPTION OF THE MORAL DEVELOPMENT PROGRAM: SUPPORTING STUDENTS' SPIRITUAL CONSISTENCY - Anggraini, Nursela; Mahariah, Mahariah (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
This research aimed to analyze the implementation of the student moral development program. The focus of the study in this research was on three things, namely planning the student moral development program, implementing the student moral development program, and evaluating the student moral development program. The research method used is qualitative based on phenomenology. The data collection techniques used were observation, interviews, and documentation studies. The data obtained was then analyzed using the Miles and Huberman technique, namely data reduction, data display, and drawing conclusions. The research results explained that the student moral development program was designed with an integrated three-stage conception. These include designing the program's TOR (Terms of Reference) by adapting the program objectives to the vision and mission of the madrasah, habituation of program rundowns such as honesty cooperative activities, Friday tausiyah, Rohis activities, tahfidz Qur'an, and anti-bullying agent programs, as well as following up up the program by carrying out program evaluation and follow-up using the goal oriented evaluation model. This coaching program forms students who had good morals, are polite, in speech and deeds, noble in behavior, wise, polite and civilized, sincere, honest and holy.